Evaluation report : The Carrick Institute Forum on the Design of Learning Environments : convened at the University of Melbourne & RMIT University, September 2007. - Jamieson, Peter (Australian Learning and Teaching Council (ALTC), 2007)
Evaluation report on The Carrick Institute Forum on the Design of Learning Environments, convened at the University of Melbourne and RMIT University in September 2007. This national professional development program was convened to prepare key university staff to support their respective institutions to better undertake the design and development of new generation learning environments. The intensive, weeklong design forum involved a multidisciplinary group of twenty academic and professional staff representing seventeen Australian universities. The forum explored the nature of the 'design' process and sought to engage participants in a process that would directly challenge their understanding of how the design of new generation learning environments could be approached.